2013
DOI: 10.1108/jhtt-06-2011-0020
|View full text |Cite
|
Sign up to set email alerts
|

Information technology diffusion in Malaysia's foodservice industry

Abstract: Purpose-The purpose of this paper is to investigate how three organizational factorsaffiliation, sufficient capital and company agerelated to 323 Malaysian foodservice companies' diffusion of six information technology (IT) applications. The IT applications, basic or advanced, respectively, represent two innovation diffusion levels, adoption and implementation. Design/methodology/approach-This study drew on a survey of chief executive officers, owners, information system/technology managers, operations manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…In the food service industries, managers use multiple ICT innovations, and differing rates of diffusion stages than was previously thought. IT adoption and implementation in this industry also related to significantly sufficient capital (Fareed Ismail et al , 2013). Tourism managers may use Internet-based marketing decision support systems.…”
Section: Organisational Usementioning
confidence: 99%
See 1 more Smart Citation
“…In the food service industries, managers use multiple ICT innovations, and differing rates of diffusion stages than was previously thought. IT adoption and implementation in this industry also related to significantly sufficient capital (Fareed Ismail et al , 2013). Tourism managers may use Internet-based marketing decision support systems.…”
Section: Organisational Usementioning
confidence: 99%
“…For example, Yuan et al (2006) found that advancements in IT in American convention and visitor bureaus did not spread uniformly across four information activity dimensions and appear to occur in five recursive and sequential stages, namely: substitution, enlargement, gestation, reconfiguration, and setback. Fareed Ismail et al (2013) investigated how three organisational factors – affiliation, sufficient capital and company age – related to 323 Malaysian foodservice companies' diffusion of six IT applications. Their study highlights multiple diffusion stages for multiple technological innovations in organisations.…”
Section: Organisational Usementioning
confidence: 99%